Dose-response relationship between internal training load and changes in performance during the preseason in youth soccer players - Figueiredo, D. H.; Figueiredo, D. H.; Moreira, A.; Gonçalves, H. R.; Dourado, A. C. (The Journal of Strength and Conditioning Research, 2021)
The aim of this study was to describe training intensity distribution based on the session rating of perceived exertion (sRPE) and heart rate (HR) methods and examine the dose-response relation between internal training load (ITL) and change in performance of 16 youth soccer players (mean ± SD age: 18.75 ± 0.68 years, height: 175.3 ± 5.5 cm, body mass: 68.7 ± 6.5 kg, and body fat: 10.7 ± 1.2%) belonging to a Brazilian first division team during a 3-week preseason. The sRPE and HR data were registered daily to calculate the ITL and the training intensity distribution, in 3 intensity zones (low, moderate, and high). The Yo-yo Intermittent Recovery Level 1 (Yo-yo IR1) was evaluated before and after experimental period. The total time spent in the low-intensity zone (HR method) was greater (p < 0.01) compared with the moderate- and high-intensity zones. No difference was observed between training intensity zones determined by the sRPE method (p > 0.05). Negative correlations were observed between weekly mean sRPE-TL (r = -0.69), Edward's-TL (r = -0.50), and change in Yo-yo IR1. Linear regression indicated that weekly mean sRPE-TL (F1;14 = 13.3; p < 0.01) and Edward's-TL (F1;14 = 4.8; p < 0.05) predicted 48.7 and 25.5% of the variance in performance change, respectively. Stepwise linear regression revealed that these 2-predictor variables (F2;13 = 18.9; p < 0.001) explained 74.5% of the variance in performance change. The results suggest that the sRPE and HR methods cannot be used interchangeably to determine training intensity distribution. Moreover, sRPE-TL seems to be more effective than the HR-based TL method to predict changes in performance in youth soccer players.